0818 Psychosis associated with sodium oxybate. (25th May 2022) - Bhattacharyya, Sarathi; Eng, Kevin; Harris, Brian; Zeidler, Michelle
Abstract: Introduction: Sodium oxybate is commonly used to treat narcolepsy with cataplexy. At the approved doses, the most common side effects are typically described as nausea, vomiting, dizziness, hypersomnia, urinary disturbances, and weight loss. Cases of medication-induced psychosis have been reported in the literature but remain exceedingly rare. We present a case of rapid-onset psychosis in a patient with systemic lupus erythematosus, which added complexity to the evaluation, treatment and clinical course. Report of Cases: The patient is a 42 year old woman with a past history of fibromyalgia, lupus and a prior diagnosis of narcolepsy evaluated for daytime hypersomnia and poor night time sleep. Prior medications included sodium oxybate which was effective; and modafinil and amphetamines which created intolerable side effects. Prior sleep studies were not available and a repeat PSG/MSLT were performed. PSG did not show sleep disordered breathing or nocturnal movements and MSLT showed an average sleep latency of 5.4 minutes and 4 SOREMs. HLA DQB10602 was positive. The patient was reinitiated on sodium oxybate and titrated to 4.5g twice nightly. A few weeks later the patient developed visual hallucinations, persecutory delusions, and insomnia for 3 days. She was admitted for an evaluation to rule out lupus cerebritis, and auto-immune vs. infectious encephalitis. MRI/MRA, lumbar puncture, as well as inflammatory markers and rheumatologic and infectious work up were unrevealing. Sodium oxybate was discontinued on the day of admission and the patient's mentation returned to baseline over the next few days. Discharge diagnosis was psychosis secondary to sodium oxybate. Conclusion: Psychosis is an extremely rare side effect of sodium oxybate therapy among patients treated for cataplectic narcolepsy. It remains a diagnosis of exclusion, and any alternative diagnoses must be explored prior to making the diagnosis of psychosis secondary to sodium oxybate, particularly in the medically complex patient. Support (If Any): None